Possible refinement of the standard treatment of esophageal cancer - Tu, Cheng-Che; Hsu, Po-Kuei (Journal of Thoracic Disease, 2018)
Mattiucci and colleagues made exquisite comments on the study published by Hwang et al. (1), summarized on the role of adjuvant chemoradiation (CRT) in treatment of esophageal cancer (2). The essential features of the referring article and the challenges of research in the topic were pointed out.